Association between Helicobacter pylori infection and metabolic syndrome and its components - Liu, Ying; Shuai, Ping; Chen, Wanjing; Liu, Yuping; Li, Dongyu (Frontiers in Endocrinology, 2023)
Background and aim The association between Helicobacter pylori (H. pylori) infection and metabolic syndrome (MetS) has been studied previously; however, the results remain controversial, which could be partly due to the different criteria used for defining MetS. We adopted five MetS criteria to provide better understanding of the association between H. pylori infection and MetS. Methods Physical examination data of 100,708 subjects were obtained from January 2014 to December 2018. MetS was defined based on five criteria including: International Diabetes Federation (IDF), The Third Report of the National Cholesterol Education Program Expert Panel, Adult Treatment Panel III (ATP III), Joint Statement of International Multi-Societies (JIS), Chinese Diabetes Society (CDS), and the Guidelines for the Prevention and Treatment of Type 2 Diabetes in China (2017 edition)(CDS DM). Multivariate logistic regression analysis was performed to elucidate the association between H. pylori infection and MetS and its components. Results The prevalence of MetS defined assessed using IDF, ATP III, JIS, CDS and CDS DM criteria was 15.8%, 19.9%, 23.7%, 8.7% and 15.4%, respectively. In males, the prevalence of MetS assessed using the five criteria in H. pylori-positive group was higher than that in negative-group; however, in females, same results were obtained using the three international criteria. In males, the prevalence of all MetS components was found to be higher in the H. pylori-positive group than those in the negative group; however, in females, only the prevalence of dyslipidemia and waist circumferences exhibited significant differences. Multivariate logistic regression analysis revealed that H. pylori infection in males was positively correlated with MetS. Additionally, H. pylori infection was found to be positively correlated with the waist circumference in the general population, and with hypertension and hyperglycemia in males. Conclusions H. pylori infection was found to be positively associated with MetS in males in China.